Ore genesis of the Chazangcuo Cu-Pb-Zn deposit in Tibet: evidence from mineralogy, fluid inclusions, S-Pb isotopes, and elemental geochemistry - Li, Yan; Wang, Jianguo; Yu, Zezhang; Wei, Shengyun; Ren, Haidong; Ma, Ming; Wang, Zhinan; Hu, Jian (Frontiers in Earth Science, 2024)
The Chazangcuo copper-lead-zinc deposit (hereafter referred to as the Chazangcuo deposit) is situated in the northern portion of the western section of the Gangdese polymetallic metallogenic belt in Tibet. Its, with ore bodies are tightlystrictly governed by Linzizong Group magmatic rocks and EW-trending faults. To elucidateThis study aims to ascertain the mineralization phases, sourceperiods, sources of ore-forming materials, metallogenic physicochemical conditions, and origingenesis of the Chazangcuo this deposit, this study conducted. Based on comprehensive field geological surveys, sampling, and microscopic examination of rock petrological and mineralogical characteristics. Furthermore, it performed, we perform qualitative and quantitative geochemical analyses of geochemical major elements, trace elements, and rare earth elements, alongside (REEs), fluid inclusions, and sulfur, and lead isotopes. The findings reveal that the Chazangcuo deposit's mineralization process of the Chazangcuo deposit can be segmenteddivided into three mineralization phasesperiods and four mineralization stages: the magmatic-hydrothermal mineralization phase, followed by the, hydrothermal mineralization phase, and then the supergene phase, encompassing themineralization periods sequentially, which consist of the mineralization stages of quartz-pyrite-sphalerite stage, the, medium-low -temperature hydrothermal sulfide stage, thesulfides, chlorite-carbonate mineral stageminerals, and finally the supergene oxidation stage.in a chronological order. The ore-forming fluids are characterized byprove to be medium-low temperatures and -temperature low densitiesdensity fluids, and the ore-forming materials bear hallmarksare characteristic of an upper crustal origin. The comprehensive analysis indicates that-derived materials. The ore-forming environment is a medium-low mineralization temperature, a shallow and weakly reducing environment. Overall, the formation of the Chazangcuo deposit is intimately associated with closely related to magmatic-hydrothermal activity. Besides, the Chazangcuo deposit exhibits, with medium-low mineralization temperatures and a shallow and mildlyweakly reducing